Analysis of the Effect of Fiber Additives on the Load-bearing Properties of Sandstone Aggregate Mixtures - Bednarek, Łukasz; Bąk, Mateusz (Civil and environmental engineering reports, 2025)
The development of road infrastructure requires an increasing use of materials that do not always meet the necessary technical requirements. In road construction, numerous methods for improving the properties of aggregates and soils are known, such as the use of fly ash, blast furnace slag, or lime. However, the amount of these additives, aimed at improving the material's parameters, can account for as much as several dozen percent of the mixture's volume. An innovative solution gaining increasing popularity is the use of fibers as dispersed reinforcement. A small addition of fibers, amounting to only 1–2%, is sufficient to significantly improve the load-bearing capacity and other mechanical properties of the material. This article presents the impact of using dispersed reinforcement in an aggregate mixture to improve its load-bearing parameters. The study utilized a 0/31.5 mm aggregate mixture enriched with various types of dispersed fibers: carbon, glass, coconut, hemp, basalt, and polypropylene. The analysis included determining the CBR (California Bearing Ratio) and shear strength of the modified material.